Enhancing Mathematical Word Problem Solving Skills: Using Bar Model Visualization Technique - Shah, Muhammad Naeem; Anjum, Fehmina; Chand, Sumaira; Tabassum, Prof. Dr. Rabia (International Research Journal of Education and Innovation, 2021)
The study purpose is to investigate the effect of Bar Model Visualization Technique on the word problem solving skills of elementary level students in mathematics. Following were the objectives of the study (i) to investigate the effect of Bar Model Visualization Technique on addition word problems-solving skills; (ii) to investigate the effect of Bar Model Visualization Technique on subtraction word problems solving skills; (iii) to investigate the effect of Bar Model Visualization Technique on multiplication word problems solving skills; (iv) to investigate the effect of Bar Model Visualization Technique on division word problems solving skills. The null hypotheses were designed to test the objectives as (i) there is no significant effect of Bar Model Visualization Technique on addition word problem solving skills; (ii) there is no significant effect of Bar Model Visualization Technique on subtraction word problem solving skills; (iii) there is no significant effect of Bar Model Visualization Technique on multiplication word problem solving skills; (iv) there is no significant effect of Bar Model Visualization Technique on division word problem solving skills. The nature of the study was experimental. Pre-test and post-test equivalent group design was used as a tool for data collection in this study. Sample of the study was 40 students (Male & Female) of Government Primary School No.2 Bab-e-Jadeed District Nowshera, Khyber Pakhtunkhwa. The sample students were divided on the basis of pretest scores by applying paired random technique in to experimental group and control group. Data were analyzed by mean, SD and t-test. It was concluded that the concepts of Bar Model Visualization Technique had significant effect on addition word problems and subtraction word problems but it has not significant effect on multiplication word problems neither division word problems. The results of the study show that Bar Model Visualization Technique had significant effect on Mathematical word problem solving skills and also the learner take interest in the subject. It provides alternative method for teacher to teach mathematics subject.